Harm reduction: evidence, impacts and challenges - Rhodes, Tim; Hedrich, Dagmar (EMCDDA scientific monograph series, 2010)
The EMCDDA's 10th scientific monograph, entitled Harm reduction: evidence, impacts and challenges provides a comprehensive overview of the harm reduction field. Part I of the monograph looks back at the emergence of harm reduction approaches and their diffusion, and explores the concept from different perspectives, including international organisations, academic researchers and drug users. Part II is dedicated to current evidence and impacts of harm reduction and illustrates how the concept has broadened to cover a wide range of behaviours and harms. Part III addresses the current challenges and innovations in the field. The core audience of the monograph comprises policymakers, healthcare professionals working with drug users, as well as the wider interested public.